2010
DOI: 10.1017/s0950268810000324
|View full text |Cite
|
Sign up to set email alerts
|

The extent of injection site infection in injecting drug users: findings from a national surveillance study

Abstract: SUMMARYInjection site infections in injecting drug users (IDUs) are associated with serious morbidity and healthcare costs. Factors associated with symptoms of these were examined through annual (2006)(2007)(2008) unlinked-anonymous survey of IDUs in England, Wales and Northern Ireland. Overall 36% (1863/5209) self-reported having a symptom with no trend over time (35 % 2006, 37 % 2007, 34 % 2008). Symptoms were less common in the North East of England ; increased with years injecting ; and were higher in wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
0
37
1
Order By: Relevance
“…Previous studies of PWID in the UK found that around one-third reported having an abscess, sore, or open wound at an injection site during the preceding year [13,14], which is higher than the level found in the present study (24%). However, while previous studies have had wider geographical coverage, they have recruited either through health services provided to people who use drugs or from community settings using simple accessibility sampling approaches [13,14].…”
Section: Symptoms Of Injection-related Bacterial Infectionscontrasting
confidence: 94%
See 1 more Smart Citation
“…Previous studies of PWID in the UK found that around one-third reported having an abscess, sore, or open wound at an injection site during the preceding year [13,14], which is higher than the level found in the present study (24%). However, while previous studies have had wider geographical coverage, they have recruited either through health services provided to people who use drugs or from community settings using simple accessibility sampling approaches [13,14].…”
Section: Symptoms Of Injection-related Bacterial Infectionscontrasting
confidence: 94%
“…However, while previous studies have had wider geographical coverage, they have recruited either through health services provided to people who use drugs or from community settings using simple accessibility sampling approaches [13,14]. The use of these approaches could have resulted in the over-sampling of higher-risk individuals.…”
Section: Symptoms Of Injection-related Bacterial Infectionsmentioning
confidence: 99%
“…These conditions can be severe, they may cause permanent health damage and may sometimes be life-threatening and they often result in complicated, expensive and long-lasting hospital treatment [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Convenient, random and respondent-driven sampling methods often result in inclusion of a negligible number of women (8). Although this reflects the fact that the prevalence of injection drug users is considerably lower in women compared with men (1, 5) yet, since women are more likely to accrue harm from drug injection (11,18), epidemiology of ensued complications should be explored more thoroughly for this gender. It is suggested that women are more likely to depend on their partner to help them with injections, hence augmenting the risk of using shared paraphernalia (32,33).…”
Section: Limitationsmentioning
confidence: 99%
“…medical complications such as infections) ascribed to complications accrued from injections (10). Injection Drug Users are at an increased risk of transmitting bacterial infections due to unsafe injection practices, and these infections are a leading cause of mortality and morbidity in this population (6,11,12).…”
Section: Introductionmentioning
confidence: 99%